Social regeneration; Community-oriented spatial strategic planning in low-income neighborhoods - Hamid Masoudi (مهندسی و مدیریت ساخت)
In recent years, urban planners have realized the challenges of a one-dimensional approach to designing and creating cities and improving the quality of life in low-income neighborhoods, and they try to use other perspectives such as psychological, economic, cultural and social perspectives in their planning. Strengthening the community-oriented and social point of view is very important in this regard, and the aim of the current research is to examine the dimensions of social regeneration in strategic spatial planning. For several years, urban regeneration and community-oriented regeneration programs have been carried out by municipalities and other organizations in different cities of the country. The current research is trying to obtain the achievements of the social regeneration approach for spatial strategic planning. After reviewing the past experiences and theoretical foundations as well as analyzing the existing models, achievements such as improving the identity, sense of belonging and dependence of the people to the localities, improving the level of social participation, social capital and people's social interactions, strengthening community-oriented planning with the involvement of people in all paths of spatial development , improving the level of people's satisfaction with urban management, spatial planners and their performance, improving the level of social sustainability of the target areas of regeneration, capacity building and social mobilization in the way of planning and design, and empowering the local community in line with urban planning and design through social regeneration for strategic spatial planning Determined.